Developing student capacity to produce digital scholarship in the humanities. (April 2022) - Schrum, Kelly
Despite the increased use of technology in higher education classrooms, we need a better understanding of pedagogical strategies that improve student ability to produce quality scholarly digital content in the humanities. This research was designed to examine student learning through scholarly digital storytelling, a technology-enhanced assessment. The researcher collected data during and after an interdisciplinary, graduate scholarly digital storytelling course, including student work, student reflections, and individual interviews, to examine experiences at key points throughout the learning process. The results indicate that this pedagogical approach, when carefully scaffolded alongside formative feedback and ongoing student support, can increase student capacity—including digital agency, problem-solving skills, and digital knowledge production skills—to produce scholarly digital work in the humanities. Students can also learn to understand the interplay between disciplinary learning and digital skills and the ways in which both are essential for scholarly communication within and beyond the classroom.